2010
DOI: 10.1002/yea.1757
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bHLH proteins regulate CIT2 expression in Saccharomyces cerevisiae

Abstract: The basic helix-loop-helix (bHLH) proteins comprise a eukaryotic transcription factor family involved in multiple biological processes. They have the ability to form multiple dimer combinations and most of them also bind a 6 bp site (E-box) with limited specificity. These properties make them ideal for combinatorial regulation of gene expression. The Saccharomyces cerevisiae CIT2 gene, which encodes citrate synthase, was previously known to be induced by the bHLH proteins Rtg1p and Rtg3p in response to mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 98 publications
(157 reference statements)
0
14
0
Order By: Relevance
“…In recent years we have reported that multiple bHLH proteins regulate the transcription of single genes in yeast (e.g., CIT2 and ENO1) (14,16). We can now add INO1 to this target list, since we showed here that Cbf1p acted in concert with the two known activators of INO1 transcription, Ino2p and Ino4p ( Fig.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In recent years we have reported that multiple bHLH proteins regulate the transcription of single genes in yeast (e.g., CIT2 and ENO1) (14,16). We can now add INO1 to this target list, since we showed here that Cbf1p acted in concert with the two known activators of INO1 transcription, Ino2p and Ino4p ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The Ino2p and Ino4p bHLH proteins are known regulators of INO1 transcription (2,67,73). We recently reported that the expression of two well-studied bHLH target genes, CIT2 and ENO1, is regulated by multiple bHLH factors (14,16). Thus, we tested whether other bHLH proteins, besides Ino2p and Ino4p, also regulate INO1 transcription.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An attractive hypothesis is that the Tye7 protein represses Ty1 antisense transcription by binding to one or more of the three E-boxes. In support of a potential repressive role of TYE7 , a previous study has reported that it could repress the transcription of the E-box-containing CIT2 gene (78). In a first model, Ty1 sense and antisense transcription could interfere in cis .…”
Section: Discussionmentioning
confidence: 88%
“…This sequence has been shown to contain the two UAS regions required for promoter regulation [71]. The CIT2 p sequence used corresponds to the largest promoter sequence used in a previous study of CIT2 regulation and consisted of the 992 bp region 5′ of the CIT2 CDS, from the −1000 to the −9 position relative to the translational start site [72]. The primers used to amplify this region were SV010 (5′-GCCGCCGAATTCGACCAATGTTAATGA-3′) and SV011 (5′-GCCGCCACTAGTTTACTAGTATTATTAAAACA-3′).…”
Section: Methodsmentioning
confidence: 99%